Dylemat wolność – bezpieczeństwo albo o pożytkach z instytucji czynności operacyjno-rozpoznawczych - Mazur, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The purpose of this article is to show a strong tension between two important values, namely freedom and security. A lawmaker has to choose a limitation of freedom to achieve security, which is very difficult. Legislator has to face with the dilemma in time of an institutional transformation. That time usually brings a radical growth of criminality. In such circumstances citizens demand from the legislator an effective fight with this serious threat. A lawmaker has to enable citizens both security and freedom by various legal institutions for example initial investigation. The initial investigation is based on a secret interfering in privacy for instance: a wire tapping by such services as police or secret service. This controversial solution has led so far to the reduction of crimes, especially organized. It can be justified by Max Weber’s ethics of responsibility. A lawmaker, however, has to protect the whole political community by some controversial institutions from the moral point of view.